Reconstructing the Role of the Marriage Guardian Based on Maqāṣid al-Sharī‘ah: Toward Substantive Justice for Women in Islamic Family Law in Indonesia - Azima Amalia; Jayusman Jayusman; Zuhraini Zuhraini; Iskandar Syukur (Fakultas Syariah Universitas Islam Negeri Sultanah Nahrasiyah Lhokseumawe, 2026)
This study aims to analyze the principles and role of the marriage guardian in Islamic marriage law in Indonesia by highlighting the relationship between the validity of the marriage contract and the protection of women. The study employs a normative legal method with a qualitative approach based on a literature review of fiqh texts, the Compilation of Islamic Law, legislation, and contemporary scholarly studies. The results show that the construction of the marriage guardian in Indonesian positive law still tends to position women as subjects dependent on the guardian’s authority, thereby creating a tension between legal justice and substantive justice particularly when rigid requirements for guardianship actually encourage unregistered marriages and weaken legal protections for women. This study finds that the concept of kāmil al-ahliyyah can serve as a reconstructive solution by establishing the full legal capacity of adult women as the primary basis for determining the need for guardianship. Through the maqāṣid al-syarī‘ah approach, the guardian is repositioned not merely as an absolute requirement but as a contextual protective instrument through the normative reinterpretation of the Compilation of Islamic Law (KHI) and the strengthening of the role of the judicial guardian. This concept enables the creation of a balance between the validity of contracts, the protection of women, and legal certainty within the Islamic family law system in Indonesia.